Compressive strength of stabilised granitic residual soil using mixture of pineapple fibre—hydrated lime - Md. Yusof, Zeety; Al-Adhami, Abdullah Mahgoob Yahya; Mohd Matore, Mohd Effendi Ewan (MDPI Open Access Journals, 2022)
Granitic Residual Soil (GRS), referring to the weathered soil from rocks, widely exists all over the world, especially in tropical regions. This type of soil is considered weak for construction due to unsaturated soils and the fact that granitic soil properties can vary from one location to another during formation. As a result, soil stabilisation is necessary. In Malaysia, pineapple fibre (PA fibre) is one of the most widely available waste materials. Chemical stabilisation technology is an attractive stabilisation technique that has been successfully used as a soil stabilising agent for many years. Hydrated lime (HL) is an activation agent and is very commonly used to replace cement application in soil stabilisation. Utilising HL and PA fibre as a soil stabilising agent is an economical and sustainable option as HL contains high pozzolanic characteristics that make it more suitable and reliable to stabilise soil, and PA fibre has high specific stiffness and strength. This study uses the replacement portion of the GRS with stabilising agents—HL and PA fibre, aiming to achieve Malaysia’s green technology goals by balancing economic expansion and environmental privilege. However, the aim of this study is to determine the effect of HL–PA fibre mixture replacement on the performance of mechanical and physical properties enhancements of GRS. GRS is the control sample whereas HL and PA fibre are used as binders. The unconfined compressive strength with the curing period was tested. The result showed that for untreated GRS, the moisture content, Atterberg limit, and specific gravity were 9.44%, 37.3%, and 2.3%, respectively, while the maximum dry density was 1.55 g/cm3 and the optimum moisture was 13.5%, according to the compaction test. Due to weathering conditions, the soil was classified using the Unified Soil Classification System (USCS) as well-graded sand soil, based on the sieve analysis. Sieved soil of 2 mm was used to stabilise the GRS mix with HL and PA fibre. The resulting UCS showed that 0 curing days increased strength by 31%, while 7 curing days increased strength by 26% before decreasing the strength by 8.4% to 9%.